The application of measurement software by quantity surveying firms in Klang Valley - Nik Fatma Arisya, Nik Yahya; Appadoo, Heshna (INTI International University, 2018)
The success of the construction industry is increasingly predicated on technology driven investments in information technology (IT) and this is expected to be even more so in the future. It is advantageous for quantity surveyors to be efficient in producing bills of quantities from measurement. Measurement software has been designed to help quantity surveyors to upgrade their way of working, making it faster and more systematic. This paper sought to identify the extent of software use at present as well as strategies to mitigate the barriers to the use of measurement software. The data for this study were collected from selected quantity surveying firms registered in Klang Valley, Malaysia through qualitative approach. The study found that large and medium firms are more likely to use measurement software as compared to small firms. The major problems identified are high cost and, required learning and training to use the software. The major benefits identified are high accuracy, speed up measurement works, and high traceability.